2012
DOI: 10.1158/0008-5472.can-12-0123
|View full text |Cite
|
Sign up to set email alerts
|

Effective Combination Therapy for Malignant Glioma with TRAIL-Secreting Mesenchymal Stem Cells and Lipoxygenase Inhibitor MK886

Abstract: The apoptotic ligand TRAIL is believed to have promise as a cancer gene therapy, yet many types of cancer, including gliomas, have exhibited resistance to TRAIL-induced apoptosis. Here, we show that therapeutic combination of the lipoxygenase inhibitor MK886 and TRAIL-secreting human mesenchymal stem cells (MSC-TRAIL) provide targeted and prolonged delivery of TRAIL both in vitro and in orthotopic mouse models of glioma. Treatment of either TRAIL-sensitive or TRAIL-resistant human glioma cells with MK886 and M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 43 publications
(47 reference statements)
0
43
0
Order By: Relevance
“…Previous studies have shown that BMSCs migrated directionally to glioma tissue (9,16). Accordingly, some studies applied BMSCs as the vector for targeted gene therapy against gliomas and obtained encouraging data (8,9). However, the mechanisms for the tropism of BMSCs towards glioma have yet to be fully elucidated and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that BMSCs migrated directionally to glioma tissue (9,16). Accordingly, some studies applied BMSCs as the vector for targeted gene therapy against gliomas and obtained encouraging data (8,9). However, the mechanisms for the tropism of BMSCs towards glioma have yet to be fully elucidated and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BMSCs) are a type of adult stem cells isolated from bone marrow. Due to their directional migration abilities towards gliomas after transplantation, they have been applied as the vectors of gene therapy against gliomas (7)(8)(9). However, the molecular mechanisms responsible for this migratory behavior have not been fully explained and require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, novel drugs are required that sensitize glioma cells to TRAIL-induced apoptosis, or new strategies are needed to overcome TRAIL resistance that can be combined with MSCs-TRAIL. Working toward these goals, different groups have explored various methods, including the use of TRAIL along with chemotherapeutic agents (Johnson et al, 2013;Kim et al, 2014), radiotherapy (Kim et al, 2010), lipoxygenase (Kim et al, 2012), and carbenoxolone (Yulyana et al, 2013). These methods have all had better therapeutic results than those using TRAIL alone.…”
Section: Msc Delivery Of Therapeutic Genesmentioning
confidence: 99%
“…The application of this system (MSCs secreting TRAIL) has advantages over some of the other engineered MSC-delivery systems since there are almost no-detectable effects on non-cancerous tissues. Promising early results are obtained not only from the investigations with animal models, but also from clinical trials carried out currently [111][112][113][114].…”
Section: Us20150086515 (2015)mentioning
confidence: 99%